The Role of Human Capital and Urbanization in Driving Economic Growth in Indonesia - Damia Liana; Rosalina Tineke Kusumawardhani (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
This study examines the impact of urbanization, education, interaction between urbanization and education, government expenditure, labor, and trade on Indonesia’s economic growth. Using the Autoregressive Distributed Lag (ARDL) approach, the analysis distinguishes the short-run and long-run effects of each variable on GDP. The results show that urbanization positively affects long-run growth through agglomeration economies, while education significantly enhances productivity in line with endogenous growth theory. However, urbanization without adequate skill improvement reduces productivity due to labor skill mismatches in urban areas. Government expenditure has a negative short-run effect but a positive long-run impact, indicating fiscal adjustment lags before investment spending stimulates growth. Meanwhile, trade shows a negative long-run relationship, reflecting dependence on imported consumer goods and low-value commodity exports. The findings highlight the importance of strengthening human capital, improving fiscal efficiency, and promoting trade policies that enhance domestic value-added to achieve inclusive and sustainable economic growth.